Academic Entrepreneurship in Theory and Practice - Hanna Nowak-Mizgalska, Aleksandra Szulczewska-Remi (eds.) (Poznań University of Economics and Business, 2022)
With the increasing interest in academic entrepreneurship (AE), an interdisciplinary and multidimensional phenomenon, this book provides insights on the different aspects of the process, especially from the CEE countries. The topics cover include the theoretical issues related to defining and understanding AE as well as the empirical research featuring aspects of AE at the organizational levels of analysis that encourage the interchange of experiences from diverse institutional environments. The audience for this book comprises researchers, policymakers and university students in the fields of management, strategy and entrepreneurship.